Putusan Mahkamah Konstitusi Terkait Batas Usia Minimal Calon Presiden dan Calon Wakil Presiden Dalam Putusan MK Nomor 90/Puu-Xxi/2023 Perspektif Etika Profesi dan Tanggung Jawab Hukum - Muyassar, Alifia Nada; Putri, Khairunnisa Wiladi; Alya, Farah; Maniari, Elsa; Pramudya, Aissyah Lintang; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Constitutional Court (MK) has a crucial role in upholding the supremacy of law and the constitution in Indonesia. However, the independence and integrity of MK judges are in the spotlight in MK Decision Number 90/PUU-XXI/2023 which changes the provisions on the age limit for presidential and vice presidential candidates. This decision has sparked controversy due to allegations of violations of the code of ethics by one of the MK judges who has a conflict of interest with the party benefiting from the decision. This study aims to analyze the effect of violations of the code of ethics by MK judges on the legitimacy and acceptance of MK decisions. The research method used is juridical-normative with a statutory regulatory approach and analysis of decisions and their impacts. The results of the study show that violations of the code of ethics can damage public trust in the MK and give rise to debate about the validity of the resulting decisions. In addition, non-compliance with the code of ethics has the potential to weaken the independence of the judiciary and create a bad precedent for the enforcement of constitutional law in the future. Therefore, a stricter oversight mechanism is needed for MK judges as well as strict enforcement of sanctions to ensure that the resulting decisions remain objective and based on the principle of justice.